2021
DOI: 10.5194/hess-2021-443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opportunities for seasonal forecasting to support water management outside the tropics

Abstract: Abstract. Advance warning of seasonal conditions has potential to assist water management in planning and risk mitigation, with large potential social, economic and ecological benefits. In this study, we explore the value of seasonal forecasting for decision making at five case study sites located in extratropical regions. The forecasting tools used integrate seasonal climate model forecasts with freshwater impact models of catchment hydrology, lake conditions (temperature, level, chemistry and ecology) and fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For example, interviews and focus groups with end users of NOAA's Climate Prediction Center climate outlook visualizations guided updates of NOAA's air temperature and precipitation color maps for improved forecast interpretability (Gerst et al, 2020). Finally, feedback from managers and end users should be sought after forecast dissemination to determine if the forecast product is being successfully implemented for decision‐making support (e.g., Jackson‐Blake et al, 2022).…”
Section: Discussion and Synthesis: Opportunities To Advance Near‐term...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, interviews and focus groups with end users of NOAA's Climate Prediction Center climate outlook visualizations guided updates of NOAA's air temperature and precipitation color maps for improved forecast interpretability (Gerst et al, 2020). Finally, feedback from managers and end users should be sought after forecast dissemination to determine if the forecast product is being successfully implemented for decision‐making support (e.g., Jackson‐Blake et al, 2022).…”
Section: Discussion and Synthesis: Opportunities To Advance Near‐term...mentioning
confidence: 99%
“…Near‐term forecasts comprise a wide range of time scales (e.g., daily, weekly, seasonal, decadal), each of which is likely associated with different end‐user goals and decisions. For example, a ship captain may be most interested in lake ice conditions over the next several hours to days when deciding whether to embark (Fujisaki‐Manome et al, 2022), while a reservoir manager may look multiple months ahead when planning water releases downstream (Jackson‐Blake et al, 2022; Turner et al, 2020). We observed a relative dearth of near‐term freshwater quality forecasts at multi‐month (seasonal) time scales (but see Mercado‐Bettín et al, 2021; Figure 6), highlighting an opportunity for the development of additional forecasts at this horizon.…”
Section: Discussion and Synthesis: Opportunities To Advance Near‐term...mentioning
confidence: 99%
“…As well as providing an easy way of deriving probabilistic forecasts, we found a real benefit of using BNs for forecasting was in stakeholder engagement and model co-development. We found that the easy and transparent visualisation of the model increased stakeholder engagement in the model development process and stakeholders' ability to correctly interpret the probabilistic predictions (Jackson-Blake et al, 2022).…”
Section: Forecasting To Support Water Managementmentioning
confidence: 93%
“…The focus of the WATExR project, a European Union project funded by the European Research Area for Climate Services (ERA4CS), was to help address this gap by developing pilot seasonal forecasting tools for lake water quality and ecology. Tools were co-developed with water managers at five catchmentlake case study sites, with four in Europe and one in South Australia (Jackson-Blake et al, 2022). Tools linked seasonal climate forecasts with models for predicting river discharge, lake water level and water temperature (Mercado-Bettín et al, 2021), water quality, algal bloom risk, and fish migration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, interviews and focus groups with end users of NOAA's Climate Prediction Center climate outlook visualizations guided updates of NOAA's air temperature and precipitation color maps for improved forecast interpretability (Gerst et al, 2020). Finally, feedback from managers and end users should be sought after forecast dissemination to determine if the forecast product is being successfully implemented for decision-making support (e.g., Jackson-Blake et al, 2022).…”
Section: Integration Of End Users Into the Forecast Processmentioning
confidence: 99%